Optimalisasi Peran Corporate Social Responsibility (CSR) Terhadap Kebijakan Ekspor Pasir Laut Dengan Prinsip Perlindungan Lingkungan - Rahayu, Dian Anggi; Ramadhani, Prastiti Suryaning; Novel, Samirah; Lestari, Widya Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Government Regulation No. 26 Year 2023 on the Management of Sedimentation Results in the Sea has raised concerns due to its potential harm to marine ecosystems and possible conflict with environmental protection principles under Law No. 32 of 2009. Using a normative juridical method, this study finds that Corporate Social Responsibility (CSR) plays a vital role in mitigating environmental and social impacts, particularly through rehabilitation and coastal community programs. However, CSR implementation remains weak due to insufficient regulatory clarity. The study recommends strengthening CSR regulations with derivative norms ensuring transparency, independent evaluation, and public involvement. It also urges a comprehensive review of Government Regulation No. 26 Year 2023 to align with environmental principles such as AMDAL, public participation, and the precautionary principle. Corporations are encouraged to embed CSR into their sustainability strategies to ensure real contributions to environmental conservation and community welfare.